Petata-petitih Masyarakat Minangkabau di Nagari Koto Baru Kecamatan Kubung Kabupaten Solok - Rahayu, Elvia; Amir, Amril; Hamidin, Hamidin (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study was to describe petatah-petitih and moral value ​​contained in each petatah-petitih that exist in society in Nagari Koto Baru Kecamatan Kubung Kabupaten Solok. The research data is moral value in petatah-petitihused by society in Nagari Koto Baru Kecamatan Kubung Kabupaten Solok. The data source of this research is the source of oral, the verbal sources arepetatah-petitih spoken by people in communication. Data were collected using interviews, recording methods and methods of record. The study's findings include two things: (1) form petatah-petitih, petatah-petitih of is including oral folklore and has implied intent of petatah-petitih is presented, in order to not feel offended, (2) moral values ​​in petatah-petitih, custom  moral values ​​can be seen through the four factors commonly called in custom, that is pasing raso, pareso, malu, and sopan. Religious moral values ​​are moral values ​​in Islam.